Vegetable gardening in small plots. - Ahmad, Siti Hajar
Space saving techniques to raise vegetables in a small garden plot include 1)growing of climbers on poles,stakes and fences 2)intercropping, 3)interplanting, 4)succession planting, 5)relay planting, and 6)short rows. Methods of establishing and maintaining the garden plot are discussed.